Anteseden dan Konsekuensi Ekonomi Sirkular Berbasis Lahan Basah di Kalimantan Selatan: Studi Etnografi (Perspektif Syariah) - Shaddiq, Syahrial; Aini, Nur (Dharma Ekonomi, 2024)
This study examines the implementation of a wetland-based circular economy in South Kalimantan, which integrates local wisdom and sharia values ​​for sustainable natural resource management. The purpose of this study is to understand how the principles of ta'awun (mutual cooperation), maslahah, and istihsan can encourage organic waste management, ecosystem conservation, and improve community welfare through a circular economy. The method used is an ethnographic study, with a qualitative approach to explore the experiences, views, and practices of local communities in implementing this concept. The results of the study indicate that a wetland-based circular economy not only provides economic and environmental benefits, but also strengthens social and religious values ​​through cross-sector collaboration involving the community, government, and the private sector, as well as the implementation of sharia instruments such as productive waqf and environmental zakat for sustainable development in South Kalimantan.